Sistem Informasi Pengolahan Data Akuntansi Pada Toko Nia Collection - Mochamad Nandi Susila; Mulyadi .; Ulfah Royan - UNiversitas BSI (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2023)
Abstrak – Nia Collection store is a business entity engaged in trading that sells various kinds of clothing from adults to children. The processing of financial reports at the Nia Collection Store is still manual or not computerized, so errors often occur in processing data or financial reports. The accounting data processing system runs at Toko Nia Collection, starting from collecting transaction evidence, journaling, general ledger, trial balance, adjusting journal, work sheet, income statement, capital change report, and balance sheet report. This study uses data collection methods by direct observation of the evidence needed in the implementation of accounting data processing information systems in Zahir Accounting 5.1 tools. The purpose of this research is to facilitate the recording of transactions that occur on the object of research.Keywords: Nia Collection Shop, Information System,, Zahir Accounting 5.1 Abstrak: Toko Nia Collection merupakan badan usaha yang bergerak dibidang perdagangan yang menjual berbagai macam pakaian dari yang dewasa hingga anak-anak. Dalam pengolahan laporan keuangan di Toko Nia Collection masih manual atau belum terkomputerisasi sehingga sering terjadi kesalahan dalam pengolahan data atau laporan keuangan. Sistem pengolahan data akuntansi berjalan pada Toko Nia Collection, mulai dari pengumpulan bukti transaksi, pembuatan jurnal, buku besar, neraca saldo, jurnal penyesuaian, neraca lajur, laporan laba-rugi, laporan perubahan modal, dan laporan neraca. Penelitian ini menggunakan metode pengumpulan data dengan pengamatan langsung terhadap bukti-bukti yang dibutuhkan dalam implementasi sistem informasi pengolahan data akuntansi pada tools zahir accounting 5.1. Tujuan dari penelitian ini untuk mempermudah pencatatan data transaksi yang terjadi pada objek penelitian. Kata kunci: Toko Nia Collection, Sistem Informasi, Zahir Accounting 5.1